Evaluation of the relatedness between the biofilm-associated genes and antimicrobial resistance among Acinetobacter baumannii isolates in the southwest Iran - Nafiseh Hosseinzadeh Shakib; Zahra Hashemizadeh; Abolfazl Rafati Zomorodi; Reza Khashei; Yeganeh Sadeghi; Abdollah Bazargani (Iranian Journal of Microbiology)
Background and Objectives: Increasing antimicrobial resistance among Acinetobacter baumannii (A. baumannii) strains poses a significant challenge, particularly in intensive care units (ICUs) where these bacteria are common causes of hospital infections. Biofilm production is recognized as a key mechanism contributing to this resistance. This study aims to explore the relationship between biofilm production, the presence of biofilm-associated genes, and antibiotic resistance patterns in A. baumannii isolates obtained from ICU patients. Materials and Methods: We collected 100 A. baumannii isolates from ICU patients at Nemazee Hospital in Shiraz, Iran. Antimicrobial susceptibility testing (AST) was performed using the Kirby-Bauer disk diffusion method, and biofilm production potential was assessed through the tissue culture plate (TCP) method. Additionally, we investigated eleven biofilm-related genes (ompA, bap, csuE, epsA, blaper-1, bfmS, pgaB, csgA, fimH, ptk, and kpsMII) in all isolates using polymerase chain reaction (PCR). The REP-PCR technique was utilized to analyze the genetic relatedness of the isolates (Fig. 4). Results: All isolates displayed multi-drug resistance, with the highest resistance rates observed against ceftazidime, cefotaxime, and trimethoprim/sulfamethoxazole (100%). Gentamicin and amikacin showed the lowest resistance rates at 70% and 84%, respectively. A total of 98% of the isolates were capable of biofilm production, with 32% categorized as strong biofilm producers. The most frequently detected biofilm-associated genes included csuE (99%), bfmS (98%), ompA (97%), and pgaB (89%). Conclusion: Biofilm production significantly contributes to the prevalence of multi-drug resistant A. baumannii strains. It is essential to implement effective antimicrobial stewardship and develop innovative anti-biofilm strategies to address this global health issue.